Rent Sharing in China: Magnitude, Heterogeneity and Drivers - Wenjing Duan; Pedro S. Martins (Institute of Labor Economics (IZA), 2019)
Do firms in China share rents with their workers? We address this question by examining firm-level panel data covering virtually all manufacturing firms over the period 2000-2007, representing an average of 200,000 firms and 54 million workers per year. We find robust evidence of rent sharing (RS): workers that would move from low- to high-profit firms would see their wages increase by about 45%. The results are based on multiple instrumental variables, including firm-specific international trade shocks. We also present a number of complementary findings that allow us to understand better the nature of RS in the country: RS is weaker in firms with more women and less educated workers; RS involves an element of risk sharing, as wages also decrease when profits fall; RS is lower in regions with more latent competition from rural workers; higher minimum wages tend to reduce RS; and, while employer labour market power reduces wages, it increases RS. Overall, despite its importance, RS in China is smaller and more symmetric than in developed economies, which reflects the weaker bargaining power of its workers and the different scope of its labour market institutions.
Keywords: J31; J41; J50; 330; wages; bargaining; monopsony